Star wars (2020), volume 5 ebook The path to victory. - Soule, Charles (Star Wars (2020), 2023)
Collects STAR WARS (2020) #26-30. The Rebel Fleet is reunited at last! Leia Organa, Mon Mothma and the other Alliance leaders send a message to the galaxy that resistance to Palpatine's rule remains as strong as ever. Meanwhile, Crimson Dawn has activated their sleeper agents across the galaxy - and two of them race to deliver a dangerous secret to the Rebel Alliance. But the Empire knows what they have stolen, and the entire Imperial Navy is in hot pursuit! Meanwhile, Threepio enters into aggressive negotiations, Luke embarks on a mission that will test his growing Jedi skills to the limit, and the rebels come to understand the true scope of the threat they face!